2001
DOI: 10.1614/0890-037x(2001)015[0453:drneoh]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Drift-Reducing Nozzle Effects on Herbicide Performance1

Abstract: Herbicide efficacy, coverage, and retention were evaluated for spray applied through Drift Guard, Turbo TeeJet, AI TeeJet, and TurboDrop drift-reducing nozzles compared to a conventional flat-fan nozzle. Percentage spray coverage detected on water-sensitive cards was greater for conventional and Drift Guard nozzles than for Turbo TeeJet, AI TeeJet, and TurboDrop nozzles. Spray without adjuvants was retained better by redroot pigweed for treatments applied with conventional and Drift Guard nozzles than Turbo Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
46
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 15 publications
7
46
0
3
Order By: Relevance
“…When applied with the AI nozzle, Array, Border, and Placement increased the D V0.1 by 17 to 23 m. Although each DCA reduced driftable droplets when applied with the AI nozzle, this reduction did not translate to in-field differences of D L or D I distance, except with Border. Ramsdale and Messersmith (2001) found no differences in control of three bioassay species among DG, TT, AI, TD, and conventional TP nozzles, despite differences in the spray coverage on water-sensitive cards.…”
Section: Resultsmentioning
confidence: 68%
“…When applied with the AI nozzle, Array, Border, and Placement increased the D V0.1 by 17 to 23 m. Although each DCA reduced driftable droplets when applied with the AI nozzle, this reduction did not translate to in-field differences of D L or D I distance, except with Border. Ramsdale and Messersmith (2001) found no differences in control of three bioassay species among DG, TT, AI, TD, and conventional TP nozzles, despite differences in the spray coverage on water-sensitive cards.…”
Section: Resultsmentioning
confidence: 68%
“…There was no effect of the water carrier volume with the FF nozzles, but the AI nozzles with the 100 L ha -1 rate improved the control of A. theophrasti (4%) and P. persicaria (8%).This is consistent with the results of Knoche (1994), who found that, with glyphosate, herbicidal performance increased as the carrier volume decreased. Ramsdale and Messersmith (2001) also indicated that glyphosate was equally or more effective in a 47 L ha -1 compared to a 190 L ha -1 spray volume. There was no effect of the spray pressure with the AI nozzles on weed control.…”
Section: Resultsmentioning
confidence: 91%
“…Derivas acidentais durante a aplicação têm potencial para provocar danos em cultivos no sistema de semeadura direta (Hemphill Jr. & Montgomery, 1981;Gelmini, 1988;Ramsdale & Messersmith, 2001;Banks & Schroeder, 2002;Lyon et al, 2003b) e no algodoeiro Lyon et al, 2003a;Miller et al, 2004), fazendo-se necessário gerar informações para a caracterização e quantificação desses efeitos. Também, a possibilidade de uso de cultivares de algodão, soja e milho geneticamente modificados para resistência ao herbicida glyphosate deverá aumentar o potencial de deriva desse produto para culturas/cultivares sensíveis.…”
Section: Introductionunclassified